Efektivitas Metode Demonstrasi dalam Meningkatkan Pemahaman Siswa - Nor Habibah; Muhammad Yasin (PT. Penerbit Tiga Mutiara, 2024)
The success of a lesson is inseparable from the selection of methods presented, one of which is using the demonstration method, where students and teachers must be actively involved in the learning process. The author describes the demonstration method in fiqh learning. 1) How is the effectiveness of the demonstration method in fiqh learning at MTs Negeri Insan Cendekia. 2) How is the effectiveness of the use of demonstration methods in student understanding of fiqh learning by using descriptive analysis so as to determine the effectiveness of the use of demonstration methods in Fiqh subjects. The findings in this study are that students show proficiency because they are able to analyse the material presented by the teacher, but there are obstacles encountered is the presence of inattentive students who are unable to answer questions because of lack of focus.